Natural flavonoids for the prevention of colon cancer: A comprehensive review of preclinical and clinical studies. Issue 12 (13th May 2019) - Afshari, Khashayar; Haddadi, Nazgol‐Sadat; Haj‐Mirzaian, Arvin; Farzaei, Mohammad Hosein; Rohani, Mohammad Mojtaba; Akramian, Freshteh; Naseri, Rozita; Sureda, Antoni; Ghanaatian, Negar; Abdolghaffari, Amir Hossein
Abstract: Flavonoids comprise a group of natural polyphenols consisting of more than 5, 000 subtypes mostly existing in fruits and vegetables. Flavonoids consumption could potentially attenuate the incidence and recurrence risk of colorectal cancers through their antiperoxidative, antioxidant, and anti‐inflammatory effects. In addition, these compounds regulate the mitochondrial function, balance the bacterial flora and promote the apoptosis process in cancerous cells. However, some previous data failed to show the effectiveness of flavonoids in reducing the risk of colorectal cancer. In this study, we have reviewed the efficacy of different flavonoids subtypes on the risk of colon cancer and molecular mechanisms involved in this process in both clinical and animal studies. In addition, we tried to elucidate the potential synergy between these compounds and current colorectal cancer treatments. Abstract : Flavonoids consumption could potentially attenuate the incidence and recurrence risk of colorectal cancers through their antiperoxidative, antioxidant, and anti‐inflammatory effects. In this study, we have reviewed the efficacy of different flavonoids subtypes on the risk for colon cancer and molecular mechanisms involved in this process in both clinical and animal studies.